Photo and Text: Media Combination in the Literary Reportage “Die Slawen von nebenan – Sorbische Reise durch Deutschland” by Karl-Markus Gauß - Khrystyna Kachak (Studien zur Deutschen Sprache und Literatur)
The purpose of the article is to study the photo-text combination in the literary reportage „Die Slawen von nebenan – Sorbische Reise durch Deutschland” by the Austrian author Karl-Markus Gauß, which integrates both linguistic and visual elements in the form of two photos: one of the cemetery in Ralbicy/Ralbitz and the other of the library in Slepo/ Schleife. Based on the theory of intermediality, literary reportage is viewed as a complex multimedia phenomenon and understood as a media combination according to Irina Rajewsky’s typology. The aim of this study is to determine the interaction between the two media and to analyze their influence on the overall effect of the literary work. It is based on the thesis that the interaction of language and image not only strengthens the documentary character of the reportage, but also opens up a new narrative dimension. In order to investigate this thesis, a comprehensive analysis of the linguistic and visual elements is carried out. The text is examined in detail with regard to its linguistic characteristics, style, structure and content. At the same time, the photographic elements – composition, lighting, color and perspective - and their placement in the text are analyzed. The qualitative study revealed that the photos serve as central content anchors, extending beyond a purely illustrative function. They establish vertical narrative structures, providing deeper insights into the rich history and cultural identity of the Sorbian community. It is emphasised that the literary reportages of K.-M. Gauss present the traditions and way of life of minorities in a special media way. Such issues are particularly interesting in the context of current social changes, as they can increase awareness of the relevance of minority histories in a globalized world.